EDUCATIONAL POLICY IN ALGERIA THROUGH THE EDUCATION LAW (Lex localis - Journal of Local Self-Government, 2025)
Schools are the fundamental pillar for establishing the Algerian character and consolidating the unity of the Algerian people. This is achieved through the principles established by the Education Law, which proposes the idea of ​​strengthening the role of schools in consolidating Algeria's image and sense of belonging, consolidating the concept of a unified collective historical identity, and establishing a modern school whose mission is to teach the culture of democracy and build the concept of citizenship by instilling a set of values. In this article, we attempt to clarify educational policies in Algeria through a review of the Education Law.